2019
DOI: 10.1007/s42399-019-00055-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antimicrobial Prescription Pattern among Paediatric Cancer Patients with Febrile Neutropenia

Abstract: Febrile neutropenia (FN) is the most common haematological toxicity associated with cytotoxic chemotherapy. Individual studies are available, but national estimates on FN are required. To describe chemotherapy-induced neutropenia, its associated infection-causing organisms, and the antimicrobials prescribed, a prospective cum retrospective study was conducted for a period of 9 months, which included 50 paediatric cancer patients less than 18 years. Patients having an absolute neutrophil count (ANC) less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…It showed 82% efficacy in imipenem and 59% in ceftazidime plus vancomycin group. 14 In a study conducted by Abraham et al, at Bharati hospital, Pune in 2019; 32% of paediatric patients suffered from febrile neutropenia and Staphylococcus species (49%) were the most common one which was positive in blood culture, 15 however in our study most of the cultures were negative and only two culture were positive for S. aureus.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It showed 82% efficacy in imipenem and 59% in ceftazidime plus vancomycin group. 14 In a study conducted by Abraham et al, at Bharati hospital, Pune in 2019; 32% of paediatric patients suffered from febrile neutropenia and Staphylococcus species (49%) were the most common one which was positive in blood culture, 15 however in our study most of the cultures were negative and only two culture were positive for S. aureus.…”
Section: Discussioncontrasting
confidence: 54%
“…Besides mucositis and mucormycosis no fungal infection was documented in our study, which is comparable to other studies. 15 Invasive fungal infections contribute significant morbidity and mortality in neutropenic patients on chemotherapy. Thus, a delay in treatment while establishing a diagnosis leads to increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were from diverse regions globally, with six (18%) conducted in the United States 2,11–15 and 28 (82%) studies in other countries (Africa, n = 1 [3%]; Asia, n = 15 [44%]; Oceania, n = 2 [6%]; Europe, n = 4 [12%]; Middle East, n = 4 [12%]; Central America, n = 1 [3%]; South America, n = 1 [3%]) 16–43 (Figure S2). Majority ( n = 21, 62%) 2,11,12,16,18,19,21,25,26,28–35,38,39,42,43 of studies utilized standard culture methods, while a smaller number ( n = 8, 24%) 13,14,20,22–24,27,41 of studies reported on newer methods such as metagenomic sequencing and PCR diagnostics (i.e., qPCR [including singleplex and multiplex], 22,23 panfungal real‐time PCR, 27 16S rRNA gene PCR, 23,24 respiratory viral panel PCR, 13,20,41 and Pneumocystis jirovecii PCR 20 ). Other assessed tests or studies included histopathology examination, 15 Aspergillus galactomannan antigen assay (GM), 15,17,20,27 (1‐3)‐β‐D‐glucan assay (BDG), 15,27 and procalcitonin and C‐reactive protein biomarkers 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies reported on the clinical course, including antimicrobial therapy. 2,11,12,[14][15][16][17][18][19][20][21]23,25,29,30,33,[35][36][37][38][39][40][41]43 The diagnostic impact on antimicrobial use was reported in only three studies. Two studies assessed the diagnostic impact of using samples from invasive procedures (i.e., BAL and video-assisted thoracoscopic surgery-biopsy) and determined that using such samples led to a change in antimicrobial management in 20.6%−49.5% 15,20 and 64.5% 15 of the cases with suspected infections, respectively.…”
Section: Assessed Outcomes For Pediatric Populationmentioning
confidence: 99%
“…Traditionally, Gram-negative bacte-ria were known as the primary causative agent of BSI in FN patients. Throughout the 1980s and 1990s, there was a decreasing incidence of Gram-negative bacteria accompanied by a relative increase in Gram-positive infection; a change attributed to factors such as better management of Gram-negative infections, prescription of prophylactic fluoroquinolones, and increased use of intravenous catheters (4,5). The current situation of distribution of bacteria in pediatric FN in our community is controversial.…”
Section: Introductionmentioning
confidence: 99%